Marketing Perspective in Social Enterprise Performance: A Bibliometric Analysis - Salqaura, Siti Alhamra; Rizca Amelia, Wan; Alfifto, Alfifto; Catur Putera Hasman, Haryaji (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
Social enterprise performance is a subject that is being intensively researched in recent years because the effects are claimed to be accelerated a country's economic development. The purpose of this study is to analyze the correlation of marketing regarding social enterprise performance so that it can present theoretical frameworks and guides for new researchers. The Scopus, Crossref, and google scholar databases were used in this research. This research uses qualitative methods from the literature review. The most cited paper is “Social Marketing: An Approach to Planned Social Change”. The most prolific years were 2015 to 2019. This research resulted in three major topics that are currently being researched, namely social marketing, enterprise, and performance. Furthermore, the results of this study also indicate future research opportunities.